ANALYSIS THE CAPACITY OF WASTE WATER TREATMENT PLANTS (WWTP) MARGASARI BALIKPAPAN CITY - PURWASARI, MEGA (KURVA S JURNAL MAHASISWA, 2014)
Lack of a wareness on the part of society on the environment in the present this is theproblem facted by cities big in Indonesia.waste in one of the important of issues thatrequire special handling due to the dischange of waste water directly into the river can leadto water pollution and environmental.cantamination can affect water quality standar ofraw water used for clean water. Waste water treatment plant(WWTP) is one of the effortsundertaken to address the problem of government and the results of these preparations canbe in use again. Balikpapan city currently has three waste water treatment plants (WWTP).Margasari waste water treatment plant is a waste water treatment plant that was built in thefirst instance that stars operation frist started in 2003. capacity in the tub equalisasi is 196, capacity in the tub aeration is 1.532 , capacity in the sedimentation tub one is 125, capacity in the sedimentation tub two is 125 , capacity in tub results of the treatedwater is 636,5 . and contruction of the building is of reinforced concrete.Analysiscalculation that produced at municipal waste water treatment plants (WWTP) margasaribalikpapan city next 15 years in 2018 is 255 /. Of the results of laboratory tests inthe laboratory local water companies (PDAM) balikpapan city on the results of wastewater treatment (WWTP) margasari on 12 may 2014 and 26 may 2014 , the results ofwaste water treatment there is an increase in the parameters of degree of acidity (pH)from 8,0 to 8,3 and chemical oxygen demand (COD) from 100 to119 but the results ofthese tests are still below the maximum levels of the water in the (WWTP) margasariappropriate standards that have been set, accordance with the regulations of the provinceof east kalimantan number 12 of 2011 on the management of water quality and waterpollution control standars of domestic waste water and the environment minister’s number112 0f 2003 on waste water quality standards.Key